A quantum version of the algebra of distributions of SL2 - Angiono, Iván Ezequiel (2018)
Let λ be a primitive root of unity of order l. We introduce a family of finite-dimensional algebras {DλN (sl2)}NεN0 over the complex numbers, such that DλN (sl2) is a subalgebra of DλM (sl2) if N < M, and DλN-1(sl2) ⊂ DλN (sl2) is a uλ(sl2)-cleft extension. The simple DλN (sl2)-modules (LN(p))0≤p